Térségi biztonsági kérdések és megoldások az afrikai kontinensen – Az Afrikai Unió és a regionális gazdasági közösségek (RECs) biztonsági architektúrája - Tarrósy, István (Afrika Tanulmányok / Hungarian Journal of African Studies, 2018)
This article discusses the need for the extension of the notion of security by drawing attention to the complexity of ‘human security’ and its daily realities across Africa. It provides an overview of the numerous struggles of the African (and external) organisations in building up an architecture, which may be capable of protecting the many interests of the populations of the continent. Several cases are presented about failures of concerted efforts, together with a growing number of success stories in terms of peacekeeping, creating and maintaining stability, which surely is key to lasting development outcomes for local livelihoods in the continent. It attempts to open up a critical eye on what can be expected for the long run from the African Union and the RECs.